Leadership development in a Representative Council of Learners (RCL) in a secondary school in the Eastern Cape - Strydom, Monica Petro (Rhodes University, Faculty of Education, Department of Education, 2017)
The purpose of this study was to answer two main research questions: How is leadership promoted on a Representative Council of Learners (RCL) and What leadership roles do learners on the council play in schools? Recent research suggests that although the democratisation of school governance has given all stakeholders a voice in how schools are being governed, it seems that learner voice is still largely silenced. Literature on this issue paints an uninspiring picture of learner under-involvement and marginalisation. In seeking underlying causes for this, this study is informed by notions of leadership for social justice. The study investigated the RCL at a public, fee-paying school in the Makana district of the Eastern Cape. By observing the daily functioning of the council, engaging with the learner leaders as well as teachers, parents and other role players, I developed a better understanding of the challenges the RCL faced as well as factors which promoted their role as learner leaders. This aided in answering the first key research question of how the RCL promotes leadership development. To answer the second key question, I needed to consider the perceptions of stakeholders concerned and how they saw the operation of the RCL. This study is situated in the interpretive research tradition and uses critical realism as its under-labourer. To support this study and to answer some of the aims of this research, Leontiev's second generation Cultural Historical Activity Theory was used. Data were collected through semi-structured interviews, questionnaires an observation and document analysis. Data analysis took the form of identifying themes which emerged from the data. These formed the basis of my discussion and I was thus able to address the main research questions. Data revealed that learner leaders in schools are mainly managers and not really leaders; that learners are still very much marginalised as leaders and that they subsequently do not have a lot of say when it comes to how their schools are governed. It further emerged that despite formal legislation and guidelines which are in place to allow for the democratic rights of learners' opinions to be heard in schools, historical and cultural forces account for parents and other role players'reluctance to allow learners to have too much of a say. I trust that the findings from this research will strengthen learner leadership structures in schools and perhaps provide guidelines on how learner leadership could be developed and managed.
Keywords: Uncatalogued